The Effect of Ryegrass Silage Feeding on Equine Fecal Microbiota and Blood Metabolite Profile - Zhu, Yiping; Wang, Xuefan; Liu, Bo; Yi, Ziwen; Zhao, Yufei; Deng, Liang; Holyoak, Reed; Li, Jing (Frontiers in Microbiology, 2021)
Silage is fed to horses in China and other areas in the world, however, knowledge about the impact of feeding silage on horse health is still limited. In the current study, twelve horses were assigned into two groups and fed silage and hay respectively for 8 weeks. High-throughput sequencing was applied to analyze fecal microbiota, while liquid chromatography–tandem mass spectrometry (LC–MS/MS) based metabolomics technique was used for blood metabolite profile to investigate the influence of feeding silage (group S) compared to feeding hay (group H) on equine intestinal and systemic health. Horses fed silage had significantly different fecal microbiota and blood metabolomes from horses fed hay. The results showed that Verrucomicrobia was significantly less abundant, whereas Rikenellaceae and Christensenellaceae were markedly more abundant in group S. The metabolomics analysis demonstrated that silage feeding significantly affected lipid metabolism and insulin resistance in horses, which might be associated with metabolic dysfunction. Furthermore, Pearson’s correlation analysis revealed that triglycerides (TG) were positively correlated with Sphingobacteriaceae, Nocardiaceae, Oscillibacter and Enterococcaceae, however, negatively correlated with Treponema, Roseburia and Lachnospiraceae. Overall, silage feeding impacted systemic metabolic pathways in horses, especially lipid metabolism. This study provides evidence of effects on horses of feeding silage, indicating a need for further investigation into the relationship of a silage based diet and equine health.